COVID-19 seroprevalence in Pakistan: a cross-sectional study. Issue 4 (6th April 2022) - Ahmad, Ahsan M; Shahzad, Khurram; Masood, Mariumn; Umar, Maida; Abbasi, Fahad; Hafeez, Assad
Abstract : Objectives: This study adapted WHO's ' Unity Study' protocol to estimate the population prevalence of antibodies to SARS CoV-2 and risk factors for developing SARS-CoV-2 infection. Design: This population-based, age-stratified cross-sectional study was conducted at the level of households (HH). Participants: All ages and genders were eligible for the study (exclusion criteria: contraindications to venipuncture- however, no such case was encountered). 4998 HH out of 6599 consented (1 individual per HH). The proportion of male and female study participants was similar. Primary and secondary outcome measures: Following were the measured outcome measures- these were different from the planned indicators (i.e. two out of the three planned indicators were measured) due to operational reasons and time constraints: - Primary indicators: Seroprevalence (population and age specific). Secondary indicators: Population groups most at risk for SARS-CoV-2-infection. Results: Overall seroprevalence of SARS-CoV-2 antibodies was 7.1%. 6.3% of individuals were IgG positive while IgM positivity was 1.9%. Seroprevalence in districts ranged from 0% (Ghotki) to 17% (Gilgit). The seroprevalence among different age groups ranged from 3.9% (0–9 years) to 10.1% (40–59 years). There were no significant differences in the overall seroprevalence for males and females. A history of contact with a confirmed COVID-19 case, urban residence and mask use were key risk factors for developing SARS-CoV-2 infection. Conclusions: This survey provides useful estimates for seroprevalence in the general population and information on risk factors for developing SARS-CoV-2 infection in the country. It is premised that similar studies need to be replicated at the population level on a regular basis to monitor the disease and immunity patterns related to COVID-19.